When Do Sudden Stops Really Hurt? - Caner, Mehmet (2012)
This paper analyzes the drivers and consequences of sudden stops of capital flows. It focuses on the impact of external vulnerability on the depth and length of sudden stop crises. The authors analyze 43 developing and developed countries between 1993 and 2006. They find evidence that external vulnerability not only significantly impacts the probability of a sudden stop crisis, but also prolongs the time it takes for growth to revert to its long-term trend once a sudden stop occurs. Interestingly, external vulnerability does not significantly impact the size of the instantaneous output effect in case of a sudden stop but prompts a cumulative output effect through significantly diminishing the speed of adjustment of output to its trend. This finding implies that countries financing a large part of their absorption externally do not suffer more ferocious output losses in a sudden stop crisis, but take longer to adapt afterward and are hence expected to suffer more protracted crises periods. Compared with previous literature, this paper makes three contributions: (i) it extends the country and time coverage relative to datasets that have previously been used to analyze related topics; (ii) it specifically accounts for time-series autocorrelation; and (iii) it provides an analysis of the adjustment path of economic growth after a sudden stop.